Making visible the invisible. Gender violence and between generations in a colombian indigenous community - Yepes Delgado, Fanny Lucía; Hernández Enríquez, Colombia (Investigación y Educación en Enfermería, 2010)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective. To assess gender violence and between generations in an Embera Indigenous reservation. Methodology. Participative Action Research Approach guided by epistemological perspective of Critical Theory, held in an Embera community of Antioquia, Colombia. Participative emphasis, meetings and workshops focused on health problems identified with the Indigenous participants. Results. There is a growing concern in the community for increased abuse between men and women, distancing and devaluation of relations between generations, and the loss of identity due to exposure to the western culture. Problem invisibilized and supported by the upbringing and education received and provided to the new generations, and the governors and leaders role in the compliance of equity rules between genders and generations. Conclusion. Violence between genders and generations is a health and educational problem that is affecting the well-being of the studied Embera community.